Effects of probiotics on selected anthropometrics and biochemical measures in overweight or obese Saudi subjects: a double-blind, placebo-controlled, randomised clinical trial - Samira M AlMalki; Hanan A Alfawaz; Turki A Binmoammar; Saleh F AlBahlei; Luluah M Al Bakr; Ahmed M Alzahrani; Salem S Alshammari; Syed Danish Hussain; Shaun Sabico; Nasser M Al-Daghri (Cambridge University Press, 2024)
Abstract Objective: This study aimed to assess the effects of multi-strain probiotics on anthropometric and biochemical measures in Saudi adults with overweight or obesity. Design: Single-centre, double-blind, placebo-controlled, randomised clinical trial. Setting: Occupational Health Clinics at King Saud University Medical City, Riyadh, Saudi Arabia. Participants: Ninety-three Saudi participants with overweight or obesity were randomly assigned to receive twice-daily doses of either placebo (n 49) or 30 × 109 CFU/g of HEXBIO® containing three Lactobacillus and three Bifidobacterium species (n 44) in a double-blind manner over a 12-week period, respectively. Both groups adhered to a hypoenergetic diet. Anthropometric measurements, glycaemic indices and lipid profiles were evaluated at baseline and post-intervention. Results: Following the 12-week intervention, no statistically significant differences were found in all between the probiotic group and placebo group comparisons, except for fat intake, where the group*time interaction showed a significant decrease in favour of the probiotic group (P = 0·02). However, significant within-group reductions were observed in the probiotic group: body weight (-0·9 kg, P = 0·02), HC (-1·5 cm, P = 0·002), energy intake (-387·3 kcal/d, P = 0·002), fasting glucose (-0·7, P = 0·002) and LDL-cholesterol (-0·7, P = 0·02). Conclusion: Consumption of multi-strain probiotic supplementation over 12 weeks significantly decreased fat intake in Saudi adults with overweight or obesity, with the probiotic group highlighting improved anthropometric and biochemical parameters. Further research is needed to evaluate the long-term clinical significance of this dietary practice and whether it has a meaningful impact on overall health beyond the placebo effect.